Ethylene-acrylate terpolymers, processes for their preparation and use

CN122958628APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510511543.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

Liu等基于铜络合物催化实现乙烯与丙烯酸甲酯的可控原子转移自由基聚合(ATRP),共聚物中的乙烯含量仅为20mol%左右(J Am Chem Soc,2001,123,12738-12739);这种金属催化工艺的一个缺点是共聚物通常含有微量的金属杂质,得到的聚合物是有色的

Benefits of technology

[0035]通过上述技术方案,本发明采用乙烯、丙烯酸甲酯a1、第二种丙烯酸酯a2进行三元共聚合,由于第二种丙烯酸酯单体与复合乳化剂(乳化剂c1和助乳化剂c2)的协同作用,有效地减小了聚合乳液的粒径,从而使乳液聚合具有细乳液聚合特征,从而大大提高了乙烯单体与乳液的接触面积,进而显著提高了乙烯在共聚物中的含量,并且,能够制备出乙烯含量在大范围内可调控的乙烯-丙烯酸酯三元共聚物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958628A_ABST
    Figure CN122958628A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of acrylic rubber, and discloses an ethylene-acrylate terpolymer, a preparation method and application thereof.The preparation method of the ethylene-acrylate terpolymer comprises the following steps: in the presence of ethylene, subjecting acrylate monomer a1, acrylate monomer a2, vulcanization monomer b, emulsifier c1, co-emulsifier c2, alkaline regulator d, solubilizer e, initiator f and water g to emulsion polymerization reaction.According to the method, the terpolymerization of ethylene and acrylate is realized at low temperature and pressure through a miniemulsion polymerization method, and in particular, the method can significantly increase the content of ethylene in the copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of acrylate rubber technology, specifically to an ethylene-acrylate terpolymer, its preparation method, and its application. Background Technology

[0002] Ethylene-acrylate rubber is a copolymer of ethylene and acrylate, possessing excellent heat aging resistance, oil resistance, cold resistance, compression set resistance, ozone resistance, and weather resistance. It is widely used in automotive parts, such as front and rear crankshaft oil seals, front and rear main shaft oil seals, power steering pump seals, transmission pump seals, and water pump seals. It is also used in the electrical industry to manufacture high-temperature and oil-resistant wires, cables, and gaskets. However, due to the high difficulty of free radical polymerization of ethylene, very harsh polymerization conditions are often required. For example, this type of rubber can be prepared by free radical copolymerization of ethylene and acrylate under high temperature (150-300℃) and high pressure (150-300MPa), with the ethylene content adjustable from 40-70 mol%. Research on achieving both under milder conditions is rarely reported. Liu et al. achieved controlled atom transfer radical polymerization (ATRP) of ethylene and methyl acrylate using copper complex catalysis, with the ethylene content in the copolymer being only about 20 mol% (J Am Chem Soc, 2001, 123, 12738-12739). A drawback of this metal-catalyzed process is that the copolymer usually contains trace amounts of metal impurities, resulting in a colored polymer. Sun Yat-sen University reported a nickel-based catalyst for the synthesis of AEM polymers via coordination polymerization (Macromolecules, 2022, 55, 3096-3105), but the polymer was predominantly ethylene, with an acrylate content of only about 10 mol%, and the coordination polymerization activity was low, resulting in a low molecular weight polymer (<10000). Therefore, a production method for ethylene-acrylate rubber with controllable composition and a mild preparation process has always been a hot topic and a challenge in industrial research. Summary of the Invention

[0003] The purpose of this invention is to provide a novel ethylene-acrylate terpolymer, its preparation method, and its application. This method achieves the terpolymerization of ethylene and acrylate at lower temperatures and pressures through a fine emulsion polymerization process. In particular, this method can significantly increase the ethylene content in the copolymer.

[0004] To achieve the above objectives, the present invention provides a method for preparing an ethylene-acrylate terpolymer, comprising: a step of emulsion polymerization of acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e, initiator f, and water g in the presence of ethylene, wherein the acrylate monomer a1 is methyl acrylate, the acrylate monomer a2 is selected from ethyl acrylate, propyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, methyl methacrylate, butyl methacrylate, and ethylene acrylate, the emulsifier c1 is selected from organic acid salts, and the co-emulsifier c2 is selected from one or more of long-chain fatty alcohols containing 10-20 carbon atoms and long-chain fatty hydrocarbons containing 10-20 carbon atoms.

[0005] Preferably, the method includes:

[0006] 1) In the presence of ethylene, acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e and water g are mixed and emulsified to obtain an emulsion.

[0007] 2) The emulsion obtained in step 1) is brought into contact with initiator f and subjected to emulsion polymerization to obtain the emulsion polymerization product;

[0008] 3) The emulsion polymerization product obtained in step 2) is brought into contact with a demulsifier and demulsified.

[0009] Preferably, based on the total mass of af, the total amount of acrylate monomer a1 and acrylate monomer a2 is 55-95% by mass, more preferably 60-92% by mass, and even more preferably 65-90% by mass.

[0010] Preferably, the mass ratio of the acrylate monomer a1 to the acrylate monomer a2 is 0.1-10:1, more preferably 0.2-5:1.

[0011] Preferably, based on the total mass of af, the amount of acrylate monomer a1 is 10-70% by mass, more preferably 15-60% by mass, and even more preferably 18-55% by mass.

[0012] Preferably, based on the total mass of af, the amount of acrylate monomer a2 is 5-70% by mass, more preferably 10-65% by mass, and even more preferably 15-60% by mass.

[0013] Preferably, the sulfurized monomer b is selected from one or more of acrylic acid compounds and maleic acid monoester compounds, and more preferably from one or more of acrylic acid, methacrylic acid and monoethyl maleate.

[0014] Preferably, based on the total mass of af, the amount of sulfur monomer b is 1-25% by mass, more preferably 2-20% by mass, and even more preferably 3-15% by mass.

[0015] Preferably, the emulsifier C1 is selected from one or more of alkyl sulfates, alkyl sulfonates and alkyl naphthalene sulfonates, and more preferably from one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, ammonium dodecyl sulfate, calcium dodecyl sulfonate and sodium dibutylnaphthalene sulfonate.

[0016] Preferably, the co-emulsifier C2 is selected from one or more of decacarbonyl alcohol, undecaneyl alcohol, dodecaneyl alcohol, tridecaneyl alcohol, tetradecaneyl alcohol, pentadecaneyl alcohol, hexadecaneyl alcohol, heptadecanol, octadecaneyl alcohol, nonadecanol, eicosane, decadecane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, octadecane, nonadecanol, and eicosane, more preferably selected from one or more of dodecaneyl alcohol, tetradecaneyl alcohol, pentadecaneyl alcohol, hexadecane, heptadecanol, octadecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, and octadecane, more preferably selected from one or more of dodecaneyl alcohol, hexadecaneyl alcohol, hexadecane, and octadecane.

[0017] Preferably, based on the total mass of af, the total amount of emulsifier C1 and co-emulsifier C2 is 0.5-10% by mass, more preferably 0.8-5% by mass, and more preferably 1-3% by mass.

[0018] Preferably, the mass ratio of the emulsifier C1 to the co-emulsifier C2 is 0.1-10:1, more preferably 0.5-2:1.

[0019] Preferably, based on the total mass of af, the amount of emulsifier c1 is 0.1-5% by mass, more preferably 0.2-2% by mass, and even more preferably 0.4-1.5% by mass.

[0020] Preferably, based on the total mass of af, the amount of the co-emulsifier C2 is 0.1-5% by mass, more preferably 0.3-3% by mass, and even more preferably 0.5-2% by mass.

[0021] Preferably, the alkalinity regulator d is selected from one or more of sodium hydroxide, sodium bicarbonate, sodium bisulfate, potassium hydroxide, potassium bicarbonate, potassium bisulfate, ammonium sulfate, ammonium bicarbonate, ethylenediamine, ethanolamine, sodium phosphate, and basic amino acids.

[0022] Preferably, based on the total mass of af, the amount of alkalinity regulator d is 0.01-2% by mass, more preferably 0.05-1% by mass, and even more preferably 0.1-0.5% by mass.

[0023] Preferably, the solubilizer e is an alkane with 5-10 carbon atoms and / or an aromatic hydrocarbon with 6-10 carbon atoms.

[0024] Preferably, based on the total mass of af, the amount of solubilizer e is 2-40% by mass, more preferably 3-30% by mass, and even more preferably 5-25% by mass.

[0025] Preferably, the amount of solubilizer e is 5-50% by mass of the total amount of acrylate monomer a1 and acrylate monomer a2, more preferably 6-40% by mass, and even more preferably 8-35% by mass.

[0026] Preferably, the initiator f is a peroxide initiator, more preferably a persulfate, and more preferably one or more of potassium persulfate, sodium persulfate, and ammonium persulfate.

[0027] Preferably, the amount of initiator f, in molar amounts, is 0.01-1% of the total amount of acrylate monomer a1 and acrylate monomer a2, more preferably 0.02-0.5%, and more preferably 0.02-0.1%.

[0028] Preferably, the ethylene pressure is 0.5-20 MPa, more preferably 1-10 MPa.

[0029] Preferably, in step 1), the emulsification temperature is 5-45℃ and the emulsification time is 0.1-3h.

[0030] Preferably, the conditions for the emulsion polymerization reaction include: a polymerization temperature of 0-100℃, preferably 40-80℃; and a polymerization time of 0.1-12 hours, preferably 2-6 hours.

[0031] Preferably, the demulsifier is an inorganic salt demulsifier, preferably one or more of calcium chloride, aluminum chloride, and magnesium chloride.

[0032] Preferably, the method further includes the steps of washing and drying the precipitated polymer after demulsification.

[0033] According to a second aspect of the present invention, an ethylene-acrylate terpolymer prepared by the method for preparing the ethylene-acrylate terpolymer described in the first aspect of the present invention is provided.

[0034] According to a third aspect of the present invention, the ethylene-acrylate terpolymer prepared by the method for preparing the ethylene-acrylate terpolymer described in the second aspect of the present invention is provided as a low-temperature resistant acrylate rubber material.

[0035] Through the above technical solution, the present invention uses ethylene, methyl acrylate a1, and a second type of acrylate a2 for ternary copolymerization. Due to the synergistic effect of the second type of acrylate monomer and the composite emulsifier (emulsifier c1 and co-emulsifier c2), the particle size of the polymer emulsion is effectively reduced, thereby giving the emulsion polymerization the characteristics of fine emulsion polymerization. This greatly increases the contact area between the ethylene monomer and the emulsion, and thus significantly increases the ethylene content in the copolymer. Furthermore, it is possible to prepare ethylene-acrylate ternary copolymers with ethylene content that can be controlled within a wide range. Attached Figure Description

[0036] Figure 1 The 1H NMR spectra of the ethylene-acrylate rubbers prepared in Examples 1, 4, 6 and Comparative Example 1 are shown.

[0037] Figure 2 Transmission electron microscope images of polymer emulsion particles in Example 6 and Comparative Example 1. Detailed Implementation

[0038] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0039] In this invention, "the content of ethylene in the copolymer" refers to the content of structural units derived from ethylene in the copolymer.

[0040] In this invention, "based on the total mass of af" means: based on the total mass of acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkaline regulator d, solubilizer e and initiator f.

[0041] According to a first aspect of the present invention, a method for preparing an ethylene-acrylate terpolymer is provided, wherein the method comprises: a step of performing an emulsion polymerization reaction in the presence of ethylene, wherein acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e, initiator f and water g, wherein the acrylate monomer a1 is methyl acrylate, the acrylate monomer a2 is selected from ethyl acrylate, propyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, methyl methacrylate, butyl methacrylate and ethylene acrylate, the emulsifier c1 is selected from organic acid salts, and the co-emulsifier c2 is selected from one or more of long-chain fatty alcohols containing 10-20 carbon atoms and long-chain fatty hydrocarbons containing 10-20 carbon atoms.

[0042] According to the present invention, an emulsion can be prepared from acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e, initiator f, and water g, and then heated to the initiation temperature to carry out the emulsion polymerization reaction. Alternatively, an emulsion can be prepared from acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e, and water g, and then contacted with initiator f to carry out the emulsion polymerization reaction. Preferably, an emulsion is prepared from acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e, and water g, and then contacted with initiator f to carry out the emulsion polymerization reaction.

[0043] In a preferred embodiment of the present invention, the method includes:

[0044] 1) In the presence of ethylene, acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e and water g are mixed and emulsified to obtain an emulsion.

[0045] 2) The emulsion obtained in step 1) is brought into contact with initiator f and subjected to emulsion polymerization to obtain the emulsion polymerization product;

[0046] 3) The emulsion polymerization product obtained in step 2) is brought into contact with a demulsifier and demulsified.

[0047] According to the present invention, preferably, the acrylate monomer a2 is selected from ethyl acrylate, butyl acrylate, methyl methacrylate and butyl methacrylate.

[0048] In one specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is ethyl acrylate.

[0049] In another specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is butyl acrylate.

[0050] In another specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is ethyl methacrylate.

[0051] In another specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is butyl methacrylate.

[0052] In another specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is tert-butyl acrylate.

[0053] In another specific embodiment of the present invention, the acrylate monomer a1 is methyl acrylate and the acrylate monomer a2 is ethylene acrylate.

[0054] According to the present invention, preferably, the total amount of acrylate monomer a1 and acrylate monomer a2 is 55-95% by mass, based on the total mass of af; more preferably, the total amount of acrylate monomer a1 and acrylate monomer a2 is 60-92% by mass, based on the total mass of af; and even more preferably, the total amount of acrylate monomer a1 and acrylate monomer a2 is 65-90% by mass, based on the total mass of af.

[0055] Based on the total mass of af, specific examples of the total amount of acrylate monomer a1 and acrylate monomer a2 used can be given, for example: 55% by mass, 56% by mass, 57% by mass, 58% by mass, 59% by mass, 60% by mass, 61% by mass, 62% by mass, 63% by mass, 64% by mass, 65% by mass, 66% by mass, 67% by mass, 68% by mass, 69% by mass, 70% by mass, 71% by mass, 72% by mass. %, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., and the range formed by any two of the above values.

[0056] According to the present invention, the amount of acrylate monomer a1 can be 10-70% by mass based on the total mass of af; preferably, the amount of acrylate monomer a1 is 15-60% by mass based on the total mass of af; more preferably, the amount of acrylate monomer a1 is 18-55% by mass based on the total mass of af.

[0057] Based on the total mass of af, specific examples of the amount of acrylate monomer a1 used can be, for example: 10% by mass, 11% by mass, 12% by mass, 13% by mass, 14% by mass, 15% by mass, 16% by mass, 17% by mass, 18% by mass, 19% by mass, 20% by mass, 21% by mass, 22% by mass, 23% by mass, 24% by mass, 25% by mass, 26% by mass, 27% by mass, 28% by mass, 29% by mass, 30% by mass, 31% by mass, 32% by mass, 33% by mass, 34% by mass, 35% by mass, 36% by mass, 37% by mass, 38% by mass. %, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, etc., as well as the range formed by any two of the above values.

[0058] According to the present invention, the amount of acrylate monomer a2 can be 10-70% by mass based on the total mass of af; preferably, the amount of acrylate monomer a2 is 10-65% by mass based on the total mass of af; more preferably, the amount of acrylate monomer a2 is 15-60% by mass based on the total mass of af.

[0059] Based on the total mass of af, specific examples of the amount of acrylate monomer a2 used can be given, for example: 10% by mass, 11% by mass, 12% by mass, 13% by mass, 14% by mass, 15% by mass, 16% by mass, 17% by mass, 18% by mass, 19% by mass, 20% by mass, 21% by mass, 22% by mass, 23% by mass, 24% by mass, 25% by mass, 26% by mass, 27% by mass, 28% by mass, 29% by mass, 30% by mass, 31% by mass, 32% by mass, 33% by mass, 34% by mass, 35% by mass, 36% by mass, 37% by mass, 38% by mass. %, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, etc., as well as the range formed by any two of the above values.

[0060] In this invention, the mass ratio of acrylate monomer a1 to acrylate monomer a2 can vary within a wide range. Preferably, the mass ratio of acrylate monomer a1 to acrylate monomer a2 is 0.1-10:1; more preferably, the mass ratio of acrylate monomer a1 to acrylate monomer a2 is 0.2-5:1; and even more preferably, the mass ratio of acrylate monomer a1 to acrylate monomer a2 is 0.3-3.5:1.

[0061] According to the present invention, the reactive groups present on the vulcanizing monomer b can react with vulcanizing auxiliaries during subsequent processing of the rubber material to achieve polymer crosslinking enhancement. Preferably, the vulcanizing monomer b is selected from one or more of acrylic acid compounds and maleic acid monoester compounds; more preferably, the vulcanizing monomer b is one or more of acrylic acid, methacrylic acid, and monoethyl maleate; even more preferably, the vulcanizing monomer b is acrylic acid and / or methacrylic acid.

[0062] According to the present invention, preferably, the amount of sulfur monomer b is 1-25% by mass based on the total mass of af; more preferably, the amount of sulfur monomer b is 2-20% by mass based on the total mass of af; and even more preferably, the amount of sulfur monomer b is 3-15% by mass based on the total mass of af.

[0063] Based on the total mass of af, specific examples of the amount of the sulfurized monomer b can be given, for example: 1 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass%, 8 mass%, 9 mass%, 10 mass%, 11 mass%, 12 mass%, 13 mass%, 14 mass%, 15 mass%, 16 mass%, 17 mass%, 18 mass%, 19 mass%, 20 mass%, 21 mass%, 22 mass%, 23 mass%, 24 mass%, 25 mass%, etc., as well as the range formed by any two of the above values.

[0064] This invention employs ethylene, methyl acrylate a1, and a second type of acrylate a2 for ternary copolymerization. Due to the synergistic effect of the second type of acrylate monomer and the composite emulsifier (emulsifier c1 and co-emulsifier c2), the particle size of the polymer emulsion is effectively reduced, thereby giving the emulsion polymerization the characteristics of fine emulsion polymerization. This greatly increases the contact area between the ethylene monomer and the emulsion, and thus significantly increases the ethylene content in the copolymer. Furthermore, it is possible to prepare ethylene-acrylate ternary copolymers with ethylene content that can be controlled over a wide range.

[0065] In this invention, the emulsifier c1 is selected from organic acid salts; more preferably, the emulsifier c1 is selected from one or more of alkyl sulfates, alkyl sulfonates and alkyl naphthalene sulfonates; even more preferably, the emulsifier c1 is one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, ammonium dodecyl sulfate, calcium dodecyl sulfonate and sodium dibutylnaphthalene sulfonate; particularly preferably, the emulsifier c1 is sodium dodecyl sulfate.

[0066] In this invention, the co-emulsifier C2 is selected from one or more of long-chain fatty alcohols containing 10-20 carbon atoms and long-chain fatty hydrocarbons containing 10-20 carbon atoms.

[0067] Examples of long-chain fatty alcohols containing 10-20 carbon atoms include: decaalkylol, undecanool, dodecanool, tridecanool, tetradecanool, pentadecanool, hexadecanool, heptadecanol, octadecanool, nonadecanol, eicosanool, etc. Among these, one or more of dodecanool, tetradecanool, pentadecanool, hexadecanool, heptadecanol, and octadecanool are preferred, and dodecanool and / or hexadecanool are more preferred.

[0068] Examples of long-chain aliphatic hydrocarbons containing 10-20 carbon atoms include: decadecane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanane, octadecane, nonadecanane, eicosane, etc. Among these, one or more of dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanane, and octadecane are preferred, and hexadecane and / or octadecane are more preferred.

[0069] In a preferred embodiment of the present invention, the co-emulsifier C2 is selected from one or more of decaalkylol, undecanoylol, dodecanoylol, tridecanoylol, tetradecanoylol, pentadecanoylol, hexadecanoylol, heptadecanol, octadecanoylol, nonadecanol, eicosanol, decadecane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, octadecane, nonadecanol, and eicosanol; preferably selected from one or more of dodecanoylol, tetradecanoylol, pentadecanoylol, hexadecanoylol, heptadecanol, octadecanoylol, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, and octadecane; more preferably selected from one or more of dodecanoylol, hexadecanoylol, hexadecane, and octadecane; and even more preferably hexadecanoylol and / or hexadecane.

[0070] In a preferred embodiment of the present invention, with the aim of further increasing the ethylene content in the copolymer, the emulsifier c1 is sodium dodecyl sulfate and the co-emulsifier c2 is hexadecane.

[0071] In another preferred embodiment of the present invention, the emulsifier c1 is sodium dodecyl sulfate and the co-emulsifier c2 is hexadecyl alcohol.

[0072] In another preferred embodiment of the present invention, the emulsifier c1 is ammonium dodecyl sulfate and the co-emulsifier c2 is hexadecyl alcohol.

[0073] In another preferred embodiment of the present invention, the emulsifier c1 is sodium dodecyl sulfonate, and the co-emulsifier c2 is dodecyl alcohol.

[0074] In another preferred embodiment of the present invention, the emulsifier c1 is sodium dibutylnaphthalenesulfonate, and the co-emulsifier c2 is octadecane.

[0075] According to the present invention, preferably, the total amount of emulsifier C1 and co-emulsifier C2 is 0.5-10% by mass, based on the total mass of af; more preferably, the total amount of emulsifier C1 and co-emulsifier C2 is 0.8-5% by mass, based on the total mass of af; and even more preferably, the total amount of emulsifier C1 and co-emulsifier C2 is 1-3% by mass, based on the total mass of af.

[0076] Based on the total mass of af, specific examples of the total amount of emulsifier c1 and co-emulsifier c2 can be given, for example: 0.5% by mass, 0.8% by mass, 1% by mass, 2% by mass, 3% by mass, 4% by mass, 5% by mass, 6% by mass, 7% by mass, 8% by mass, 9% by mass, 10% by mass, etc., as well as the range formed by any two of the above values.

[0077] According to the present invention, the amount of emulsifier C1 can be 0.1-5% by mass based on the total mass of af; preferably, the amount of emulsifier C1 is 0.2-2% by mass based on the total mass of af; more preferably, the amount of emulsifier C1 is 0.4-1.5% by mass based on the total mass of af.

[0078] Based on the total mass of af, specific examples of the amount of emulsifier c1 can be given, for example: 0.1% by mass, 0.2% by mass, 0.3% by mass, 0.4% by mass, 0.5% by mass, 0.6% by mass, 0.7% by mass, 0.8% by mass, 0.9% by mass, 1% by mass, 1.1% by mass, 1.2% by mass, 1.3% by mass, 1.4% by mass, 1.5% by mass, 1.8% by mass, 2% by mass, 2.5% by mass, 2.8% by mass, 3% by mass, 3.5% by mass, 4% by mass, 4.5% by mass, 5% by mass, etc., as well as the range formed by any two of the above values.

[0079] According to the present invention, the amount of co-emulsifier C2 can be 0.1-5% by mass based on the total mass of af; preferably, the amount of co-emulsifier C2 is 0.3-3% by mass based on the total mass of af; more preferably, the amount of co-emulsifier C2 is 0.5-2% by mass based on the total mass of af.

[0080] Based on the total mass of af, specific examples of the amount of the co-emulsifier c2 can be given, for example: 0.1% by mass, 0.2% by mass, 0.3% by mass, 0.4% by mass, 0.5% by mass, 0.6% by mass, 0.7% by mass, 0.8% by mass, 0.9% by mass, 1% by mass, 1.1% by mass, 1.2% by mass, 1.3% by mass, 1.4% by mass, 1.5% by mass, 1.8% by mass, 1.9% by mass, 2% by mass, 2.2% by mass, 2.5% by mass, 2.8% by mass, 3% by mass, 3.5% by mass, 4% by mass, 4.5% by mass, 5% by mass, etc., as well as the range formed by any two of the above values.

[0081] In this invention, the mass ratio of emulsifier c1 to co-emulsifier c2 is preferably 0.1-10:1; more preferably, the mass ratio of emulsifier c1 to co-emulsifier c2 is 0.5-2:1; and even more preferably, the mass ratio of emulsifier c1 to co-emulsifier c2 is 0.5-1:1.

[0082] According to the present invention, preferably, the alkalinity regulator d is selected from one or more of sodium hydroxide, sodium bicarbonate, sodium bisulfate, potassium hydroxide, potassium bicarbonate, potassium bisulfate, ammonium sulfate, ammonium bicarbonate, ethylenediamine, ethanolamine, sodium phosphate, and basic amino acids; more preferably, the alkalinity regulator d is selected from one or more of sodium bicarbonate, sodium bisulfate, potassium bicarbonate, potassium bisulfate, and ammonium bicarbonate; even more preferably, the alkalinity regulator d is selected from sodium bicarbonate.

[0083] According to the present invention, preferably, the amount of alkalinity regulator d is 0.01-2% by mass based on the total mass of af; more preferably, the amount of alkalinity regulator d is 0.05-1% by mass based on the total mass of af; and even more preferably, the amount of alkalinity regulator d is 0.1-0.5% by mass based on the total mass of af.

[0084] Based on the total mass of af, specific examples of the dosage of the regulator d can be, for example, 0.01 mass%, 0.02 mass%, 0.03 mass%, 0.04 mass%, 0.05 mass%, 0.06 mass%, 0.07 mass%, 0.08 mass%, 0.09 mass%, 0.1 mass%, 0.15 mass%, 0.2 mass%, 0.25 mass%, 0.3 mass%, 0.4 mass%, 0.5 mass%, 0.6 mass%, 0.7 mass%, 0.8 mass%, 0.9 mass%, 1 mass%, 1.5 mass%, 2 mass%, etc., as well as the range formed by any two of the above values.

[0085] According to the present invention, the solubilizer e increases the solubility of ethylene gas. The solubilizer e is preferably an alkane with 5-10 carbon atoms and / or an aromatic hydrocarbon with 6-10 carbon atoms.

[0086] Preferably, the alkane with 5-10 carbon atoms is selected from one or more of n-pentane, n-hexane, cyclohexane, n-heptane, n-octane, and n-decane.

[0087] Preferably, the aromatic hydrocarbon with 6-10 carbon atoms is selected from one or more of benzene, toluene, xylene, ethylbenzene, n-propylbenzene, and isopropylbenzene.

[0088] According to the present invention, preferably, the amount of solubilizer e is 2-40% by mass based on the total mass of af; more preferably, the amount of solubilizer e is 3-30% by mass based on the total mass of af; and even more preferably, the amount of solubilizer e is 5-25% by mass based on the total mass of af.

[0089] Based on the total mass of af, specific examples of the amount of solubilizer e used can be, for example, 2% by mass, 3% by mass, 4% by mass, 5% by mass, 6% by mass, 7% by mass, 8% by mass, 9% by mass, 10% by mass, 11% by mass, 12% by mass, 13% by mass, 14% by mass, 15% by mass, 16% by mass, 17% by mass, 18% by mass, 19% by mass, 20% by mass, 21% by mass, 22% by mass, 23% by mass, 24% by mass, 25% by mass, 26% by mass, 27% by mass, 28% by mass, 29% by mass, 30% by mass, 32% by mass, 35% by mass, 38% by mass, 40% by mass, etc., as well as the range formed by any two of the above values.

[0090] In a preferred embodiment of the present invention, the amount of solubilizer e is 5-50% by mass of the total amount of acrylate monomer a1 and acrylate monomer a2; more preferably, the amount of solubilizer e is 6-40% by mass of the total amount of acrylate monomer a1 and acrylate monomer a2; particularly preferably, the amount of solubilizer e is 8-35% by mass of the total amount of acrylate monomer a1 and acrylate monomer a2.

[0091] According to the present invention, the pressure of the ethylene can be 0.5-20 MPa; preferably, the pressure of the ethylene is 1-10 MPa; more preferably, the pressure of the ethylene is 3-10 MPa.

[0092] According to the present invention, in step 1), the emulsification temperature can be 5-45°C, and the emulsification time can be 0.1-3h, preferably 0.25-1h.

[0093] In this invention, the emulsification is preferably carried out under stirring, and the stirring speed can be 50-2000 rpm, preferably 300-10000 rpm.

[0094] According to the present invention, in step 2), the emulsion obtained in step 1) is brought into contact with the initiator f and undergoes an emulsion polymerization reaction.

[0095] In this invention, the initiator f can be a peroxide initiator, preferably a persulfate, and more preferably one or more of potassium persulfate, sodium persulfate and ammonium persulfate.

[0096] According to the present invention, preferably, the amount of initiator f, in molar amounts, is 0.01-1% of the total amount of acrylate monomer a1 and acrylate monomer a2; more preferably, the amount of initiator f, in molar amounts, is 0.02-0.5% of the total amount of acrylate monomer a1 and acrylate monomer a2; even more preferably, the amount of initiator f, in molar amounts, is 0.02-0.1% of the total amount of acrylate monomer a1 and acrylate monomer a2.

[0097] The amount of initiator f, expressed in molar parts, is a specific example of the total amount of acrylate monomer a1 and acrylate monomer a2. Examples include, for instance, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.9%, 1%, etc., as well as any range of any two of the above values.

[0098] According to the present invention, the amount of water g can be selected according to the total amount of acrylate monomer a1 and acrylate monomer a2. For example, the ratio of the mass of water g to the total mass of acrylate monomer a1 and acrylate monomer a2 can be 1-20:1, preferably 2-10:1, and more preferably 3-8:1.

[0099] According to the present invention, the conditions for the emulsion polymerization reaction include: a polymerization temperature of 0-100°C and a polymerization time of 0.1-12h; preferably, the conditions for the emulsion polymerization reaction include: a polymerization temperature of 40-80°C and a polymerization time of 2-6h.

[0100] In this invention, the emulsion polymerization reaction is preferably carried out under stirring, and the stirring speed can be 50-2000 rpm, preferably 300-10000 rpm.

[0101] According to the present invention, the demulsifier can be any of the reagents commonly used in the art for demulsification, such as inorganic salt demulsifiers, preferably one or more of calcium chloride, aluminum chloride and magnesium chloride.

[0102] According to the present invention, preferably, the method further includes the steps of washing and drying the precipitated polymer after demulsification.

[0103] The washing and drying processes described above can be performed using conventional methods in the field, and will not be elaborated upon here.

[0104] According to a second aspect of the present invention, an ethylene-acrylate terpolymer prepared by the method for preparing the ethylene-acrylate terpolymer described in the first aspect of the present invention is provided.

[0105] This invention employs ethylene, methyl acrylate a1, and a second type of acrylate a2 for ternary copolymerization. Due to the synergistic effect of the second type of acrylate monomer and the composite emulsifier (emulsifier c1 and co-emulsifier c2), the particle size of the polymer emulsion is effectively reduced, thereby giving the emulsion polymerization the characteristics of fine emulsion polymerization. This greatly increases the contact area between the ethylene monomer and the emulsion, and thus significantly increases the ethylene content in the copolymer. Furthermore, it is possible to prepare ethylene-acrylate ternary copolymers with ethylene content that can be controlled over a wide range.

[0106] According to a third aspect of the present invention, the ethylene-acrylate terpolymer prepared by the method described in the first aspect of the present invention is provided as a low-temperature resistant acrylate rubber material.

[0107] The present invention will be described in detail below through embodiments, but the present invention is not limited to the following embodiments.

[0108] The molar contents of ethylene, acrylate, and sulfurized monomers in the copolymer were determined by proton nuclear magnetic resonance spectroscopy. In this invention, the testing equipment and conditions used were: a Bruker Avance II 400 nuclear magnetic resonance spectrometer, deuterated chloroform as the solvent, and a test temperature of 25°C.

[0109] The particle size of the emulsion was determined using a particle size analyzer. In this invention, the testing equipment and conditions used were: a Malvern nanoparticle size and zeta potential analyzer. The emulsion before demulsification was diluted 1000 times and then run stably for 30 seconds at 25°C before measurement. The measurement was performed three times to obtain the average particle size.

[0110] The Tg of the copolymer was determined using differential scanning calorimetry (DSC). In this invention, the testing equipment and conditions used were: a Mettler DSC 3 differential scanning calorimeter, with the test sample subjected to nitrogen protection at a temperature of 10 °C / min. -1 The temperature was increased from room temperature to 200°C and held at that temperature for 5 minutes to eliminate thermal history, and then increased at a rate of 10°C / min. -1 The temperature was reduced to -100℃ at a rate of 10℃·min. -1 The temperature was increased to 200℃ at a certain rate, and the glass transition temperature Tg of the copolymer was tested according to the second heating curve.

[0111] Comparative Example 1

[0112] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 50g of methyl acrylate, 2.5g of acrylic acid, 0.5g of sodium dodecyl sulfate (emulsifier), 0.1g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to the reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 1.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. Then, 0.3g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 1.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 45g of ethylene-acrylate copolymer. The polymer composition and properties are shown in Table 1.

[0113] Comparative Example 2

[0114] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 65g of methyl acrylate, 2.5g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 0.75g of hexadecane (co-emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. Then, 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 57g of ethylene-acrylate copolymer. The polymer composition and properties are shown in Table 1.

[0115] Comparative Example 3

[0116] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 65g of ethyl acrylate, 2.5g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to the reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. Then, 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 57g of ethylene-acrylate copolymer. The polymer composition and properties are shown in Table 1.

[0117] Comparative Example 4 (corresponding to Example 3)

[0118] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 20g of methyl acrylate, 40g of ethyl acrylate, 2.5g of methacrylic acid, 0.5g of ammonium dodecyl sulfate (emulsifier), 0.1g of sodium bicarbonate (alkalinity regulator), 5g of n-hexane (solvent), and 400g of water were added to the reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 5.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.3g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 5.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 72g of ethylene-acrylate copolymer. The polymer composition and properties are shown in Table 1.

[0119] Comparative Example 5 (corresponding to Example 4)

[0120] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 35g of methyl acrylate, 25g of butyl acrylate, 10g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to the reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 67g of ethylene-acrylate copolymer. The polymer composition and properties are shown in Table 1.

[0121] Example 1

[0122] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 35g of methyl acrylate, 20g of ethyl acrylate, 5.0g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 0.75g of hexadecane (co-emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 68g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0123] Compared with Comparative Examples 1 and 2, it can be seen that the addition of two types of acrylates, along with the use of a co-emulsifier, can significantly reduce the particle size of the emulsion product, thereby increasing the ethylene content in the polymer.

[0124] Example 2

[0125] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 15g of methyl acrylate, 45g of ethyl acrylate, 5.0g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 1.0g of hexadecane (co-emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0MPa, and stirring was started at 300rpm for 30 minutes to complete emulsification. 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 76g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0126] Compared with Example 1, it can be seen that adjusting the relative ratio of methyl acrylate and ethyl acrylate can further increase the ethylene content.

[0127] Example 3

[0128] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 20g of methyl acrylate, 40g of ethyl acrylate, 2.5g of methacrylic acid, 0.5g of ammonium dodecyl sulfate (emulsifier), 0.5g of cetyl alcohol (co-emulsifier), 0.1g of sodium bicarbonate (alkalinity regulator), 5g of n-hexane (solvent), and 400g of water were added to the reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 5.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.3g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 5.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 78g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0129] Compared with Comparative Example 4, it can be seen that after adding the co-emulsifier, the emulsion exhibits significant fine emulsion characteristics, and the mass transfer area with ethylene is significantly increased, thus the ethylene content of the copolymer is significantly increased.

[0130] Example 4

[0131] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 35g of methyl acrylate, 25g of butyl acrylate, 10g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 1.5g of hexadecane (co-emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 69g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0132] Compared with Comparative Example 5, the addition of the co-emulsifier resulted in a significantly fine emulsion characteristic, with the ethylene content of the copolymer noticeably increasing even at relatively low ethylene pressures (3.0 MPa). Furthermore, the use of butyl acrylate as monomer a2 further helps to lower the glass transition temperature of the copolymer.

[0133] Example 5

[0134] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 50g of methyl acrylate, 80g of butyl acrylate, 5.0g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 1.0g of hexadecane (co-emulsifier), 0.25g of sodium bicarbonate (alkalinity regulator), 15g of toluene (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0MPa, and stirring was started at 300rpm for 30 minutes to complete emulsification. 0.5g of ammonium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. During the reaction, ethylene was continuously introduced to maintain a constant gas phase pressure of 5.0MPa. After 5 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 130g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0135] Example 6

[0136] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 120g of methyl acrylate, 35g of ethyl acrylate, 15g of acrylic acid, 1.5g of sodium dodecyl sulfate (emulsifier), 2.0g of hexadecane (co-emulsifier), 1g of sodium bicarbonate (alkalinity regulator), 50g of n-hexane (solvent), and 500g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 10MPa, and stirring was started at 500rpm for 20 minutes to complete emulsification. 0.2g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 10MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 195g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0137] Figure 1 The images show the 1H NMR spectra of the ethylene-acrylate rubbers prepared in Examples 1, 4, 6, and Comparative Example 1. In the spectra, the peak at a chemical shift of 3.6 ppm is the characteristic peak of -OCH3 in methyl acrylate, the peak at 1.2-1.3 ppm is the characteristic peak of -CH2- in ethylene, and the peak at 0.8-0.9 ppm is the characteristic peak of -CH3 in butyl acrylate. Figure 1 It can be seen that the ethylene content in the products of Examples 1, 4 and 6 of the present invention is significantly higher than that in Comparative Example 1, indicating that by introducing a second type of acrylate monomer such as ethyl acrylate and butyl acrylate, the ethylene content in the ethylene-acrylate terpolymer can be significantly increased.

[0138] Figure 2 These are transmission electron microscope images of the polymer emulsion particles in Example 6 and Comparative Example 1, obtained by... Figure 2 It can be seen that the emulsion product of Example 6 has a smaller and more uniform particle size, which is significantly different from the large and agglomerated product of Comparative Example 1. This indicates that controlling the emulsion particle size is an important factor in increasing the ethylene content in the copolymer.

[0139] Example 7

[0140] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 50g of methyl acrylate, 80g of tert-butyl acrylate, 5.0g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 1.0g of hexadecane (co-emulsifier), 0.25g of sodium bicarbonate (alkalinity regulator), 15g of toluene (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0MPa, and stirring was started at 300rpm for 30 minutes to complete emulsification. 0.5g of ammonium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. During the reaction, ethylene was continuously introduced to maintain a constant gas phase pressure of 5.0MPa. After 5 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 118g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0141] Example 8

[0142] The emulsion polymerization reaction was carried out in a 3L reactor. At room temperature, 35g of methyl acrylate, 20g of ethylene acrylate, 5.0g of acrylic acid, 0.75g of sodium dodecyl sulfate (emulsifier), 0.75g of hexadecane (co-emulsifier), 0.15g of sodium bicarbonate (alkalinity regulator), 10g of n-hexane (solvent), and 400g of water were added to a reactor filled with ethylene gas. The ethylene pressure in the gas phase was adjusted to 3.0 MPa, and stirring was started at 300 rpm for 30 minutes to complete emulsification. 0.5g of sodium persulfate (initiator) was added, and the temperature was raised to 60℃ to begin polymerization. Ethylene was continuously introduced during the reaction to maintain a constant gas phase pressure of 3.0 MPa. After 3 hours of reaction, the ethylene in the reactor was vented, the polymer emulsion was collected, and the emulsion was broken with calcium chloride solution. The product was washed and dried to obtain 59g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0143] Example 9

[0144] The method of Example 6 was followed, except that the emulsifier was replaced with 1.5 g of sodium dodecyl sulfonate and the co-emulsifier was replaced with 2.0 g of dodecyl alcohol, while other conditions remained the same, to obtain 186 g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0145] Example 10

[0146] The procedure was carried out according to Example 6, except that the emulsifier was replaced with 1.8 g of sodium dibutylnaphthalenesulfonate and the co-emulsifier was replaced with 3.0 g of octadecane, while other experimental conditions remained the same, to obtain 180 g of ethylene-acrylate terpolymer. The polymer composition and properties are shown in Table 1.

[0147] Table 1

[0148]

[0149] As shown in Table 1, conventional emulsion polymerization (Comparative Examples 1 and 3-5) cannot obtain copolymers with high ethylene content under relatively low ethylene pressure conditions. This is because the solubility of ethylene in the emulsion is limited, and the large particle size of conventional emulsions results in insufficient contact area with ethylene, leading to inadequate ethylene mass transfer and its inability to fully participate in the copolymerization reaction.

[0150] Secondly, as shown in Table 1, by using the second type of acrylate monomer a2 with a higher carbon number in combination with emulsifier c1 and co-emulsifier c2, a fine emulsion with a smaller particle size (usually less than 80 nm) can be formed. The number of particles in the emulsion increases significantly, thereby greatly improving the mass transfer area with ethylene, allowing ethylene to fully participate in the copolymerization reaction and increasing the ethylene content in the copolymer.

[0151] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing an ethylene-acrylate terpolymer, characterized in that, The method includes the step of carrying out an emulsion polymerization reaction of acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, basicity regulator d, solubilizer e, initiator f and water g in the presence of ethylene. Wherein, the acrylate monomer a1 is methyl acrylate, and the acrylate monomer a2 is selected from one of ethyl acrylate, propyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, methyl methacrylate, butyl methacrylate, and vinyl acrylate. The emulsifier c1 is selected from organic acid salts, and the co-emulsifier c2 is selected from one or more of long-chain fatty alcohols containing 10-20 carbon atoms and long-chain fatty hydrocarbons containing 10-20 carbon atoms.

2. The method according to claim 1, wherein, The method includes: 1) In the presence of ethylene, acrylate monomer a1, acrylate monomer a2, sulfur monomer b, emulsifier c1, co-emulsifier c2, alkalinity regulator d, solubilizer e and water g are mixed and emulsified to obtain an emulsion. 2) The emulsion obtained in step 1) is brought into contact with initiator f and subjected to emulsion polymerization to obtain the emulsion polymerization product; 3) The emulsion polymerization product obtained in step 2) is brought into contact with a demulsifier and demulsified.

3. The method according to claim 2, wherein, Based on the total mass of af, the total amount of acrylate monomer a1 and acrylate monomer a2 is 55-95% by mass, preferably 60-92% by mass, and more preferably 65-90% by mass. Preferably, the mass ratio of the acrylate monomer a1 to the acrylate monomer a2 is 0.1-10:1, more preferably 0.2-5:

1.

4. The method according to any one of claims 1-3, wherein, Based on the total mass of af, the amount of acrylate monomer a1 is 10-70% by mass, preferably 15-60% by mass, and more preferably 18-55% by mass; Preferably, based on the total mass of af, the amount of acrylate monomer a2 is 5-70% by mass, more preferably 10-65% by mass, and even more preferably 15-60% by mass.

5. The method according to any one of claims 1-3, wherein, The sulfurized monomer b is selected from one or more of acrylic acid compounds and maleic acid monoester compounds, preferably one or more of acrylic acid, methacrylic acid and monoethyl maleate; Preferably, based on the total mass of af, the amount of sulfur monomer b is 1-25% by mass, more preferably 2-20% by mass, and even more preferably 3-15% by mass.

6. The method according to any one of claims 1-3, wherein, The emulsifier C1 is selected from one or more of alkyl sulfates, alkyl sulfonates and alkyl naphthalene sulfonates, preferably one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, ammonium dodecyl sulfate, calcium dodecyl sulfonate and sodium dibutylnaphthalene sulfonate; Preferably, the co-emulsifier C2 is selected from one or more of decacarbonyl alcohol, undecaneyl alcohol, dodecaneyl alcohol, tridecaneyl alcohol, tetradecaneyl alcohol, pentadecaneyl alcohol, hexadecaneyl alcohol, heptadecanol, octadecaneyl alcohol, nonadecanol, eicosane, decadecane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, octadecane, nonadecanol, and eicosane, more preferably selected from one or more of dodecaneyl alcohol, tetradecaneyl alcohol, pentadecaneyl alcohol, hexadecane, heptadecanol, octadecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecanol, and octadecane, more preferably selected from one or more of dodecaneyl alcohol, hexadecaneyl alcohol, hexadecane, and octadecane; Preferably, based on the total mass of af, the total amount of emulsifier c1 and co-emulsifier c2 is 0.5-10% by mass, preferably 0.8-5% by mass, and more preferably 1-3% by mass; Preferably, the mass ratio of the emulsifier C1 to the co-emulsifier C2 is 0.1-10:1, more preferably 0.5-2:

1.

7. The method according to claim 6, wherein, Preferably, based on the total mass of af, the amount of emulsifier c1 is 0.1-5% by mass, preferably 0.2-2% by mass, and more preferably 0.4-1.5% by mass; Preferably, based on the total mass of af, the amount of the co-emulsifier C2 is 0.1-5% by mass, more preferably 0.3-3% by mass, and even more preferably 0.5-2% by mass.

8. The method according to any one of claims 1-3, wherein, The alkalinity regulator d is selected from one or more of sodium hydroxide, sodium bicarbonate, sodium bisulfate, potassium hydroxide, potassium bicarbonate, potassium bisulfate, ammonium sulfate, ammonium bicarbonate, ethylenediamine, ethanolamine, sodium phosphate, and basic amino acids. Preferably, based on the total mass of af, the amount of alkalinity regulator d is 0.01-2% by mass, more preferably 0.05-1% by mass, and even more preferably 0.1-0.5% by mass.

9. The method according to any one of claims 1-3, wherein, The solubilizer e is an alkane with 5-10 carbon atoms and / or an aromatic hydrocarbon with 6-10 carbon atoms; Preferably, based on the total mass of af, the amount of solubilizer e is 2-40% by mass, more preferably 3-30% by mass, and even more preferably 5-25% by mass; Preferably, the amount of solubilizer e is 5-50% by mass of the total amount of acrylate monomer a1 and acrylate monomer a2, more preferably 6-40% by mass, and even more preferably 8-35% by mass.

10. The method according to any one of claims 1-3, wherein, The initiator f is a peroxide initiator, preferably a persulfate, and more preferably one or more of potassium persulfate, sodium persulfate and ammonium persulfate; Preferably, the amount of initiator f, in molar amounts, is 0.01-1% of the total amount of acrylate monomer a1 and acrylate monomer a2, more preferably 0.02-0.5%, and more preferably 0.02-0.1%.

11. The method according to any one of claims 1-3, wherein, The ethylene pressure is 0.5-20 MPa, preferably 1-10 MPa.

12. The method according to claim 2, wherein, In step 1), the emulsification temperature is 5-45℃ and the emulsification time is 0.1-3h.

13. The method according to any one of claims 1-3, wherein, The conditions for the emulsion polymerization reaction include: a polymerization temperature of 0-100℃, preferably 40-80℃; and a polymerization time of 0.1-12 hours, preferably 2-6 hours.

14. The method according to claim 2, wherein, The demulsifier is an inorganic salt demulsifier, preferably one or more of calcium chloride, aluminum chloride, and magnesium chloride.

15. The method according to claim 2, wherein, The method also includes washing and drying the precipitated polymer after demulsification.

16. The ethylene-acrylate terpolymer prepared by the method for preparing the ethylene-acrylate terpolymer according to any one of claims 1-15.

17. The application of the ethylene-acrylate terpolymer prepared by the method according to any one of claims 1-15 as a low-temperature resistant acrylate rubber material.